A 3D endometrial organotypic model simulating the acute inflammatory decidualisation initiation phase with epithelial induction of the key endometrial receptivity marker, integrin αVβ3. Issue 4 (25th August 2021) - Fraser, R; Smith, R; Lin, C -J
Abstract: STUDY QUESTION: Is it possible to develop a simplified physiological in vitro system representing the key cell-types associated with a receptive endometrial phenotype? SUMMARY ANSWER: We present a new concept to investigate endometrial receptivity, with a 3D organotypic co-culture model to simulate an early and transient acute autoinflammatory decidual status that resolves in the induction of a receptive endometrial phenotype. WHAT IS KNOWN ALREADY: Embryo implantation is dependent on a receptive uterine environment. Ovarian steroids drive post-ovulation structural and functional changes in the endometrium, which becomes transiently receptive for an implanting conceptus, termed the 'window of implantation', and dysregulation of endometrial receptivity is implicated in a range of reproductive, obstetric, and gynaecological disorders and malignancies. The interactions that take place within the uterine microenvironment during this time are not fully understood, and human studies are constrained by a lack of access to uterine tissue from specific time-points during the menstrual cycle. Physiologically relevant in vitro model systems are therefore fundamental for conducting investigations to better understand the cellular and molecular mechanisms controlling endometrial receptivity. STUDY DESIGN, SIZE, DURATION: We conducted an in vitro cell culture study using human cell lines and primary human cells isolated from endometrial biopsy tissue. The biopsy tissue samples were obtained from three women attending gynaecological outpatient departments in NHS Lothian. The work was carried out between December 2016 and April 2019, at the MRC Centre for Reproductive Health, Queen's Medical Research Institute, University of Edinburgh. PARTICIPANTS/MATERIALS, SETTING, METHODS: An endometrial stromal cell (ESC) line, and endometrial epithelial cells (EECs) isolated from endometrial biopsy tissue and expanded in vitro by conditional reprogramming, were used throughout the study. Immunocytochemical and flow cytometric analyses were used to confirm epithelial phenotype following conditional reprogramming of EECs. To construct an endometrial organotypic co-culture model, ESCs were embedded within a 3D growth factor-reduced Matrigel structure, with a single layer of conditionally reprogrammed EECs seeded on top. Cells were stimulated with increasing doses of medroxyprogesterone acetate, cAMP and oestradiol, in order to induce ESC decidual transformation and endometrial receptivity. Decidual response and the induction of a receptive epithelial phenotype were assessed by immunocytochemical detection and quantitative in-cell western analyses, respectively. MAIN RESULTS AND THE ROLE OF CHANCE: A transient up-regulation of the interleukin-33 receptor protein, ST2L, was observed in ESCs, indicating a transient autoinflammatory decidual response to the hormonal stimulation, known to induce receptivity gene expression in the overlying epithelium. Hormonal stimulation increased the EEC protein levels of the key marker of endometrial receptivity, integrin αVβ3 (n = 8; * P < 0.05; *** P < 0.0001). To our knowledge, this is the first demonstration of a dedicated endometrial organotypic model, which has been developed to investigate endometrial receptivity, via the recapitulation of an early decidual transitory acute autoinflammatory phase and induction of an epithelial phenotypic change, to represent a receptive endometrial status. LIMITATIONS, REASONS FOR CAUTION: This simplified in vitro ESC-EEC co-culture system may be only partly representative of more complex in vivo conditions. WIDER IMPLICATIONS OF THE FINDINGS: The 3D endometrial organotypic model presented here may offer a valuable tool for investigating a range of reproductive, obstetric, and gynaecological disorders, to improve outcomes for assisted reproductive technologies, and for the development of advances in contraceptive methods. STUDY FUNDING/COMPETING INTEREST(S): This work was supported in part by a Medical Research Council Centre Grant (project reference MR/N022556/1). R.F. was the recipient of a Moray Endowment award and a Barbour Watson Trust award. C.-J.L. is a Royal Society of Edinburgh Personal Research Fellow, funded by the Scottish Government. The authors have no conflicts of interest to declare.